2011
DOI: 10.1074/jbc.m111.231571
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS10 Protein Interacts with Fibrillin-1 and Promotes Its Deposition in Extracellular Matrix of Cultured Fibroblasts

Abstract: Autosomal recessive and autosomal dominant forms of WeillMarchesani syndrome, an inherited connective tissue disorder, are caused by mutations in ADAMTS10 (encoding a secreted metalloprotease) and FBN1 (encoding fibrillin-1, which forms tissue microfibrils), respectively, yet they are clinically indistinguishable. This genetic connection prompted investigation of a potential functional relationship between ADAMTS10 and fibrillin-1. Specifically, fibrillin-1 was investigated as a potential ADAMTS10 binding part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
171
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(179 citation statements)
references
References 37 publications
(51 reference statements)
5
171
1
2
Order By: Relevance
“…6 Although Weill-Marchesani patients are opposite to Marfan patients in outward appearance, the syndromes share a common molecular mechanism, which is defective fibrillin-1 microfibrils. 33,73,77 Further supporting a role for ADAMTS10 in microfibril function, co-localization of ADAMTS10 and fibrillin-1 has been shown by immunohistochemistry of human skin 33,73 and ADAMTS10 has been shown to promote microfibril formation in cell culture. 73 Specific and high-affinity binding of ADAMTS10 to fibrillin-1 has been demonstrated by affinity blotting assays, affinity pull-down assays, and surface plasmon resonance.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…6 Although Weill-Marchesani patients are opposite to Marfan patients in outward appearance, the syndromes share a common molecular mechanism, which is defective fibrillin-1 microfibrils. 33,73,77 Further supporting a role for ADAMTS10 in microfibril function, co-localization of ADAMTS10 and fibrillin-1 has been shown by immunohistochemistry of human skin 33,73 and ADAMTS10 has been shown to promote microfibril formation in cell culture. 73 Specific and high-affinity binding of ADAMTS10 to fibrillin-1 has been demonstrated by affinity blotting assays, affinity pull-down assays, and surface plasmon resonance.…”
mentioning
confidence: 99%
“…33,73,77 Further supporting a role for ADAMTS10 in microfibril function, co-localization of ADAMTS10 and fibrillin-1 has been shown by immunohistochemistry of human skin 33,73 and ADAMTS10 has been shown to promote microfibril formation in cell culture. 73 Specific and high-affinity binding of ADAMTS10 to fibrillin-1 has been demonstrated by affinity blotting assays, affinity pull-down assays, and surface plasmon resonance. 33,73 The binding site on fibrillin-1 for ADAMTS10 overlaps with the binding site for other ADAMTS proteins, 33 suggesting competition for the fibrillin-1 binding site or complex formation with other microfibril-associated proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MMPs degrade collagen and elastin in ECM and degradation of collagen is one of the most important events in invasion and metastasis. 29 32 Kutz et al 33 showed that there was a direct interaction between ADAMTS10 and fibrillin-1 in ECM. Like other ADAMTS, ADAMTS10 mutations may change biomechanical features of ECM in animals.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there are some reports regarding noncatalytic activities of ADAMTSs. Mammalian ADAMTS10 participates in microfibril biogenesis through its binding to fibrillin-1, in which the catalytic activity of ADAMTS10 appears not to be involved (Kutz et al 2011). ADAMTS4 binds and colocalizes with fibronectin at the cell surface, where fibronectin can inhibit ADAMTS4 activity as an aggrecanase (Hashimoto et al 2004).…”
Section: Discussionmentioning
confidence: 99%